A High‐Rate and Ultrastable Sodium Ion Anode Based on a Novel Sn4P3‐P@Graphene Nanocomposite. Issue 3 (20th September 2017) - Xu, Yaolin; Peng, Bo; Mulder, Fokko M.
Abstract: Phosphorus and tin phosphide based materials that are extensively researched as the anode for Na‐ion batteries mostly involve complexly synthesized and sophisticated nanocomposites limiting their commercial viability. This work reports a Sn4 P3 ‐P (Sn:P = 1:3) @graphene nanocomposite synthesized with a novel and facile mechanochemical method, which exhibits unrivalled high‐rate capacity retentions of >550 and 371 mA h g −1 at 1 and 2 A g −1, respectively, over 1000 cycles and achieves excellent rate capability (>815, ≈585 and ≈315 mA h g −1 at 0.1, 2, and 10 A g −1, respectively). Abstract : A Sn4 P3 ‐P (Sn:P = 1:3) @graphene nanocomposite synthesized via a novel and facile mechanochemical method is reported, which exhibits unrivalled high‐rate capacity retentions of >550 and 371 mA h g −1 at 1 and 2 A g −1, respectively, over 1000 cycles and achieves excellent rate capability (>815, ≈585 and ≈315 mA h g −1 at 0.1, 2, and 10 A g −1, respectively).